Using the systemological basis and information entropy function in the study at uncertainty conditions of system-structured objects - Kozulia, T.V.; Kozulia, M.M. (Вопросы атомной науки и техники, 2022)
In the article substantiated the expediency of introducing the basics of systemological analysis in modeling and structuring of studies of complex objects, which allows to establish conditions for the implementation of a certain target function, which is responsible for the state and functionality of the investigated object in certain conditions of the environment, taking into account the macrostate of the complex system, through experiments of microstates, and its changes in the system “object – the environment” regarding the state of external systems using an entropy func-tion according to a consistent analysis of uncertainties and their solution to establish conditions for the stabilization of the object or achieve the goal of regulation situations based on information synergetics. It was concluded that, proposed comprehensive entropy-synergy analysis of the determination of the state “the investigated system – the environment” and changes in the consequence of process transformations in systemic objects in conditions of certain uncertainty does not require additional research, characteristic of known estimates for the criteria in widespread mathematical means decision-making.